A preliminary study of the reliability and validity of the Posterior Standing Overhead Arm Reach (SOAR) test as a measure of functional hip extension motion. (October 2022) - Grimes, Jason; Wager, Justin; Goldfarb, Jon; Bauer, Paul; Ferraro, Patrick; Loken, Michelle; Lynch, Robert; Stegmann, Tyler
Abstract: Background: Current clinical tests do not provide a method to reliably measure closed chain hip extension. We developed the Posterior Standing Overhead Arm Reach (SOAR) test for this purpose. Objectives: This was a preliminary intrarater and interrater reliability and validity study of the Posterior SOAR test as a measure of functional hip extension. Design: Cross-sectional. Method: Hip extension on the Posterior SOAR test was measured with a standard goniometer independently by two examiners. The test was then repeated using three-dimensional (3D) motion capture. Intraclass correlation coefficients (ICC) were used to determine the intrarater and interrater reliability of the goniometric measure and Pearson correlations were used to assess the relationship between measures obtained via goniometry and 3D motion capture. Results: Fifty hips were assessed in 25 (14 female, 11 male) asymptomatic participants (mean age = 24.0 years, SD = 1.1). Intrarater reliability (ICC2, 3 ) was 0.80 (95% CI = 0.68–0.88) for Examiner 1 and 0.77 (95% CI = 0.64–0.86) for Examiner 2, indicating excellent reliability. The standard error of the measure (SEM90 ) ranged from 2.5° to 3.0° with a minimal detectable change (MDC90 ) of 3.5° to 4.2°. Interrater reliability was good with ICC = 0.65 (95% CI = 0.36–0.80). Pearson correlations were significant with low to moderate associations (r = 0.36, P  = 0.009; r = 0.51, P  < 0.001). Conclusions: The Posterior SOAR test demonstrated excellent intrarater reliability, good interrater reliability, and low to moderate associations with 3D motion capture. The Posterior SOAR test has the potential to provide a reliable and accurate assessment of closed chain hip extension. Highlights: Current clinical examination tests do not offer a good measure of functional hip extension motion. We developed a novel test, the Posterior Standing Overhead Arm Reach (SOAR) test to address this need. The Posterior SOAR test demonstrated excellent intrarater and good interrater reliability. Measures on the Posterior SOAR test had low to moderate associations with 3D motion analysis. The Posterior SOAR test offers a functional measure of hip extension feasible for clinical practice.